Desenvolvimento de nanocompósitos de amido/palygorskita modificada com íons de prata via casting contínuo - Vanderlei, Rafael Marques (Universidade Federal de São Carlos, 2019)
The food industry has invested cheap and efficient technologies capable of providing fresh and additive-free food products. One of the possible solutions is the use of antimicrobial active packaging that ensures the protection of foods against pathogens without affecting the product quality. In this work, palygorskite (PAL) was modified with Ag+ ions and used to obtain an antimicrobial nanocomposite film having starch as a polymer matrix. The Ag-modified PAL (PAL-Ag) was obtained by ion exchange and the production of nanocomposite films by continuous and bench casting. The clay mineral and nanocomposite films were characterized structurally, and the films had their optical and mechanical properties measured. The antimicrobial efficiency of PAL-Ag and films were evaluated against E. coli and S. aureus. Structural characterizations confirmed the fibrous-like morphology of the PAL crystals, with an average length of 1.1 ± 0.7 μm, average diameter of 62.8 ± 30.2 nm and a specific surface area of 116.5 ± 1.3 m2 g-1. The Ag adsorption was observed to occur as a two-step process and a maximum adsorption of 9.56 mg g-1 was reached after 24 h. The antimicrobial activity assays showed that PAL-Ag presented satisfactory antimicrobial activity against both bacteria. The nanocomposites made by continuous casting exhibited an excellent barrier against ultraviolet light; however, they displayed a drop of transparency to visible light. Mechanical characterizations evidenced that the use of continuous casting remarkably increased the tensile strength and elastic modulus of starch/PAL-Ag nanocomposites by 9.5 and 17.8 times in relation to the pure starch film, respectively. A consistent antimicrobial activity was not observed by the nanocomposites containing PAL-Ag at 1–10 wt.%. This study allowed the development of an antimicrobial palygorskite that could be potentially used in antimicrobial active packaging, and suitably paved the way for scaled-up production of starch/palygorskite films from solution casting.
Development of nanocomposites from starch/silver íon modified palygorskite by continuous casting
Keywords: Amido de milho; Íons de Prata; Nanocompósito; Palygorskita; Casting; Corn starch; Nanocomposites; Palygorskite; Silver ions; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS